2016
DOI: 10.1016/j.rboe.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of endoprosthesis in the treatment of bone tumors

Abstract: ObjectivesEvaluate the functional grade of these patients and to identify the types of complications found that influenced the average life span of endoprostheses the functions of the operated limb.MethodsWe analyzed 14 post-operative cases of endoprosthesis, patients with malignant bone tumors and aggressive benign bone tumors submitted to surgery between 2004 and 2014. The evaluation system used was proposed by Enneking, recommended by the Musculoskeletal Tumor Society (MSTS), in addition to the radiologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…After resection of major bone and soft tissues for a lower extremity sarcoma, the loss of sensory [58], motor [7], and proprioceptive [18] systems may disrupt physiological systems, delaying the transmission of sensory data to the central nervous system. Therefore, an appropriate timely response to activate postural muscle groups and maintain balance and posture may not be formulated [28][29][30].…”
Section: Tumor Subgroupsmentioning
confidence: 99%
“…After resection of major bone and soft tissues for a lower extremity sarcoma, the loss of sensory [58], motor [7], and proprioceptive [18] systems may disrupt physiological systems, delaying the transmission of sensory data to the central nervous system. Therefore, an appropriate timely response to activate postural muscle groups and maintain balance and posture may not be formulated [28][29][30].…”
Section: Tumor Subgroupsmentioning
confidence: 99%
“…These studies have shown good results. The MSTS [ 16 ] is a reliable tool for assessing functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…in such case, the tests are conducted on chosen samples with the same kind and size of defects as the analysed parts. The obtained measurements lead to conclusions concerning the parameters of whole group of parts [7][8][9].…”
Section: Introductionmentioning
confidence: 99%